Beam size dependency of a laser-induced plasma in confined regime: Shortening of the plasma release. Influence on pressure and thermal loading. (March 2021) - Rondepierre, Alexandre; Ünaldi, Selen; Rouchausse, Yann; Videau, Laurent; Fabbro, Rémy; Casagrande, Olivier; Simon-Boisson, Christophe; Besaucéle, Hervé; Castelnau, Olivier; Berthe, Laurent
Highlights: Reducing of the laser spot size to shorten the plasma release duration. Plasma pressure release model with a dependency to the laser spot size. Laser-matter interaction in confined regime applied to laser shock processes. Shock waves attenuation and plasticized depth regarding the spot size. Melt affected zone and thermal damages induced by the plasma. Abstract: Processes using laser-shock applications, such as Laser Shock Peening or Laser Stripping require a deep understanding of both mechanical and thermal loading applied. We hereby present new experimental measurements of the plasma pressure release regarding its initial dimension, which depends on the laser beam size. Our data were obtained through shock waves' velocity analysis and radiometric assessments. A new model to describe the adiabatic release behavior of a laser-induced plasma with a dependency to the beam size is developed. The results and the associated model exhibit that the plasma release duration is shortened with smaller laser spots. As a consequence, with chosen smaller laser spots (0.6 mm to 1 mm), the thermal loading applied during the plasma lifetime will also decrease. These new results shall help for a better understanding of laser-matter interaction for laser-shock applications by giving more accurate plasma profiles. Thus, process simulations can be improved as well. Eventually, by considering recent developments with high-power Diode Pumped Solid-State lasers (DPSS), we now expect to develop a new configuration for LSP which could be applicable both without any thermal coating and deliverable by an optical fiber.